Spectrophotometric Characterization of Some Doped Pr(III) Systems with O, N and S Containing Ligands - Pandey, H.K.; Chawla, Gourav; Gakhar, Seema (Asian Journal of Chemistry, 2010)
The present paper is concerned with studies on electronic spectral parameters, viz., Judd Ofelt parametrers (Tλ), nephelauxetic ratio (β), bonding parameter (b½) and symmetry parameter (T4/T6). These parameters are evaluated for doped Pr(III) ion with various organic reagents having O, N and S as donor atoms in M-L nteraction and the change in symmetry around Pr(III) ion is discussed.